BRAC annual report, 1999 - BRAC (© BRAC, 2016)
1. Into the next millennium 2. BRAC's mission 3. BRAC at a glance 3. BRAC: from the beginning 4. Rural development programme 5. Health, nutrition, and population programme 6. BRAC education programme 7. BRAC urban programme 8. Research and evaluation 9. Support programmes 10. Financial statements